Evaluation of PSMA PET/CT imaging using a 68Ga-HBED-CC ligand in patients with prostate cancer and the value of early pelvic imaging. Issue 6 (June 2015) - Kabasakal, Levent; Demirci, Emre; Ocak, Meltem; Akyel, Reşit; Nematyazar, Jamal; Aygun, Aslan; Halac, Metin; Talat, Zubeyir; Araman, Ahmet
<x xml:space="preserve">Abstract</x> Purpose The aim of the study was to evaluate the diagnostic value of the prostate-specific membrane antigen (PSMA) ligand 68Ga-HBED-CC (PSMA PET/CT) in patients with prostate cancer and evaluate the value of early imaging of the pelvis. Materials and methods The files of 28 patients were retrospectively evaluated. All patients had a histopatological confirmation of prostate cancer. PSMA PET/CT images were obtained at 5 and 60 min after injection from all patients. Results Intense pathologic radiotracer uptake was observed in 23 patients (77%) at the site of primary tumour. Lymph node metastases were detected in 10 patients (36%) and bone metastases were detected in seven patients (25%). Bone scan (n=25) results revealed metastatic bone lesions in four patients, equivocal results in nine patients and normal results in 12 patients. PSMA PET/CT confirmed bone metastases in all four patients. Pathologic radiotracer uptake in PSMA PET/CT scans was observed only in one patient among those who had equivocal bone scans. PSMA PET/CT showed additional bone lesions in two patients who had a normal bone scan. When we compared early and late pelvic images we found no difference in the number of lesions detected. The maximum standardized uptake value (SUVmax) for primary tumour, lymph nodes and bone metastases was significantly higher in late images. Conclusion PSMA PET/CT imaging seems to be a valuable imaging modality for evaluation of primary prostate cancer and it seems to have potential for the detection of lymph node and bone metastases. Early images 5 min p.i. can help to better distinguish between urinary bladder (before tracer accumulation occurs) and tumour lesions.